2020
DOI: 10.1016/j.funeco.2019.100899
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of arbuscular mycorrhizal fungal spore traits along an aridity gradient, and responses to experimental rainfall manipulation

Abstract: Spore size, colour and melanin content are hypothesised to be functional in relation to environmental stress. Here, we studied AM fungal spores in arid environments of Australia and in an experimental platform simulating altered rainfall. We used microscopy and image analysis to measure spore colour and size, and a quantitative colorimetric assay to estimate melanin content in spores. In arid sites, melanin content tended to increase with increasing aridity. We observed a large range of spore colours at all si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Despite a great deal of effort in investigating the effects of climatic variables and grazing on above-ground community and nutrient cycling (Post and Pedersen, 2008;Tang et al, 2019a;Wang et al, 2019;Lv et al, 2020), little is known about their interacting effects on the below-ground community, particularly at the global scale. Much of the work has been primarily conducted in mesocosm experiments through the manipulation of temperature (Hawkes et al, 2008;Zhang et al, 2019), rainfall (Deveautour et al, 2019), or both (Sun et al, 2013) at very local scales. Data collected from 233 sites worldwide revealed the key role of climate in explaining the global pattern of AMF root colonization (Soudzilovskaia et al, 2015), for example, showing that plant root colonization by AMF peaked at sites with warm growing season temperatures and declined at sites with cooler or hotter growing seasons.…”
Section: Climatementioning
confidence: 99%
“…Despite a great deal of effort in investigating the effects of climatic variables and grazing on above-ground community and nutrient cycling (Post and Pedersen, 2008;Tang et al, 2019a;Wang et al, 2019;Lv et al, 2020), little is known about their interacting effects on the below-ground community, particularly at the global scale. Much of the work has been primarily conducted in mesocosm experiments through the manipulation of temperature (Hawkes et al, 2008;Zhang et al, 2019), rainfall (Deveautour et al, 2019), or both (Sun et al, 2013) at very local scales. Data collected from 233 sites worldwide revealed the key role of climate in explaining the global pattern of AMF root colonization (Soudzilovskaia et al, 2015), for example, showing that plant root colonization by AMF peaked at sites with warm growing season temperatures and declined at sites with cooler or hotter growing seasons.…”
Section: Climatementioning
confidence: 99%
“…These traits, and others, are responsive to climatic change (Fernandez et al ). For example, mycorrhizal fungi also vary in melanin content (Wright et al ), and increases in mycorrhizal fungal melanin have been linked to variation in water availability (Deveautour et al ). Increased melanin can also reduce fungal decomposition (Fernandez et al , Fernandez and Kennedy ) and potentially reduce carbon storage (Clemmensen et al ), thus likely feeding back to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Our generally weaker models on ECM fungi can be explained by the following reasons: (i) we probably did not measure those environmental variables that really influence these species in the region, (ii) it is not yet clear which of these species form a guild and have similar environmental requirements, and (iii) it is highly probable that our model on all ECM fungi contains several guilds (species) that are driven principally by different environmental drivers. Deveautour et al (2020) also suggested numerous guilds within ECM communities. It would be especially worthwhile for ECM fungi to find the environmental requirements of single species using linear regression models.…”
Section: Proofs Of Concordant Species Responsementioning
confidence: 92%